Research on the Design of Chinese Traditional Festivals in Motion Graphics - Huo, Binbin; Liu, Jinmiao (Transactions on Social Science, Education and Humanities Research, 2023)
Chinese traditional festivals are the cultural treasures of the Chinese nation, with rich cultural connotations and spiritual values. value. They are also the distinguishing mark of the Chinese people from other countries. The rapid development of modern society has brought us a lot of convenience, but also brought us a lot of problems, such as traditional festivals by the impact of foreign cultures, fast-paced lifestyle, resulting in more and more neglect of the traditional festivals and culture of attention and importance. Therefore, in the era of information explosion, fragmented communication and rapid changes in visual aesthetics due to the popularity of the Internet and video-screen-based smart terminals, it is especially necessary to enhance the infectious force of traditional festivals through motion graphics to make them more attractive. Moreover, compared with the traditional plane static visual point of view, dynamic graphic symbols are more vivid, and there is also a lot of space for exploration of communication channels, so the festival graphics to explore new ways of expression is also in line with the trend of the times and the future development trend.